Editorial: Plant Genome-Epigenome Integrity Under Environmental Stress - Casati, Paula (2020)
Plants, due to their sessile life style, need to cope with different environmental stresses to allow proper growth and development. DNA, in association with histones, is packaged into chromatin. Several changes in chromatin structure, such as post-translational modifications of histones and DNA methylation strongly affect chromatin accessibility. In past years, it has been demonstrated that biotic and abiotic stresses trigger changes in chromatin structure, allowing modification of transcriptional programs and modulation of genome structure. Chromatin compaction and its accessibility to various factors, such as transcription factors or DNA repair enzymes, regulate transcriptional activity and also DNA repair efficiency. Chromatin remodelers, histone readers/modifiers and DNA methylases/demethylases are among the predominant factors that contribute to genome and epigenome dynamics.